2019
DOI: 10.15763/issn.2642-2387.2017.3.2.24-61
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Whiteness on the Group Socialization of Fraternity Men

Abstract: This study was constructed as a qualitative analysis to understand how racial attitudes are socialized within members of traditionally White fraternities through a critical examination of participants’ narratives on race. Narratives from seven participants were presented to identify five subcategories which were divided into two major themes for analysis: (a) Regulatory Behavior and (b) the Role of Racially Segregated Environments in Perpetuating White Supremacy. This study used institutional theory as a theor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…The limited qualitative scholarship on this topic underscores that fraternity men in particular are skilled at minimizing the importance of and the need to think about race (Joyce, 2018;Joyce & Cawthorn, 2017;Morgan et al, 2015), together with targeting or rendering invisible those who identify as part of the queer community (e.g., Duran et al, 2021;Giacalone, 2018). For instance, discussions of openness to diversity are frequently front and center during the recruitment of new members.…”
Section: Fraternal Organizations and Openness To Diversitymentioning
confidence: 99%
See 2 more Smart Citations
“…The limited qualitative scholarship on this topic underscores that fraternity men in particular are skilled at minimizing the importance of and the need to think about race (Joyce, 2018;Joyce & Cawthorn, 2017;Morgan et al, 2015), together with targeting or rendering invisible those who identify as part of the queer community (e.g., Duran et al, 2021;Giacalone, 2018). For instance, discussions of openness to diversity are frequently front and center during the recruitment of new members.…”
Section: Fraternal Organizations and Openness To Diversitymentioning
confidence: 99%
“…Similarly, when it comes to sexuality, research has demonstrated how members may actively work against the recruitment of queer men due to fears of becoming known as a queer chapter on campus-worries that are present in fraternities broadly (Giacalone, 2018), including culturally based organizations . As evident in Joyce and Cawthorn's (2017) research on the group socialization of fraternity men, white fraternity men additionally struggle to determine what is racially insensitive language and behaviors. Likewise, heterosexual fraternity men are also likely to ostracize members who they perceive as not embodying heteronormative and hypermasculine ideals (Duran et al, 2021;Giacalone, 2018).…”
Section: Fraternal Organizations and Openness To Diversitymentioning
confidence: 99%
See 1 more Smart Citation
“…White student leaders will avoid topics of race or assume post-racial perspectives when Students of Color are present and engage and use racial epithets when they are absent (Picca & Feagin, 2007). White students engage in racial joking as the most common example of backstage racism and do not actively label these behaviors as racist (Cabrera, 2014a;Joyce & Cawthon, 2017). Also, White student leaders can frame themselves as victims of racial diversity in their campus environment in primarily White spaces (Cabrera, 2014b;2014c).…”
Section: Whiteness In White Student Leadersmentioning
confidence: 99%
“…White students in highly racially homogenous spaces, such as fraternities, report few conversations about race and little reflection on their racial identities (Joyce & Cawthon, 2017). To promote engagement, reflection, and anti-racist action among White students, scholars have advanced strategies including intergroup dialogue programs, workshops, academic coursework, and co-curricular opportunities (Grier-Reed et al, 2017;Reason, 2015).…”
Section: Learning About White Racial Identity and Whitenessmentioning
confidence: 99%